Analisis Sentimen Tournament Bali Major Dengan Metode Long Short Term Memory - Alwansyah, Izhari; Garno, Garno; Irawan, Agung Susilo Yuda (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2024)
Along with the growth of technological advances and the high availability of electronic devices, the video game industry has increased rapidly because people can play video games on computers, laptops, tablet PCs, consoles or smartphones. One of the popular games that are widely played is Dota 2. The number of players and competition in this game created an electronic sport or what is often called esport. One of the big tournaments that has been held is the Bali Major tournament in Indonesia. However, unfortunately this competition received various criticisms from the public, many felt disappointed because this big tournament was not worth the ticket price set. So this has led to various public sentiments through social media. Analyzing the sentiment of twitter users towards the opinion of the Bali Major tournament itself can be an option. Therefore, this research conducted a sentiment analysis of public opinion on the Bali Major tournament as an evaluation of the next tournament. Based on research that has been conducted using 1257 tweet data as a dataset, the LSTM algorithm can perform sentiment classification with the best model getting an accuracy value of 80% and f1-score 80%. This research proves that by applying sentiment analysis techniques, information about positive and negative public sentiment is obtained as evaluation material that needs to be done to optimize technical constraints and services provided.